Rancang Bangun Asisten Virtual untuk Layanan Bengkel Berbasis Retrieval-Augmented Generation dan Tool Calling - Patrick Ardian Yoga Purnomo; Dwi Budi Santoso (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The development of Artificial Intelligence (AI) has created new opportunities for Small and Medium Enterprises (SMEs) to improve customer service quality through communication automation. C Maestro Workshop in Semarang still handles customer inquiries manually through telephone and messaging applications, resulting in delayed responses to service cost inquiries, service reservations, and vehicle repair status updates. These services also depend on staff availability and cannot be provided consistently on a 24-hour basis, leading to inefficient customer service and potentially reducing customer satisfaction. This study aims to design and develop a Retrieval-Augmented Generation (RAG)-based virtual assistant utilizing the OpenRouter Application Programming Interface (API) to address these issues. The system was developed using a TypeScript-based client-server architecture running on the Node.js runtime environment. The RAG approach was implemented through a context injection mechanism by integrating the workshop's internal knowledge base, which includes service information, estimated service costs, Frequently Asked Questions (FAQ), initial diagnostic guidance, and other supporting information, into the system prompt of the Large Language Model (LLM). In addition, the system implements a tool-calling mechanism that enables the virtual assistant to perform business functions such as service reservations, vehicle repair status inquiries, and complaint escalation to mechanics. Operational data are stored in an SQLite database, while the user interface is provided through a web-based chat application with Server-Sent Events (SSE) support to deliver real-time responses. The evaluation results indicate that the system is capable of generating relevant responses based on the knowledge base, automating the service reservation process, and escalating requests beyond its capabilities. This study contributes by developing a virtual assistant architecture that integrates Retrieval-Augmented Generation (RAG) based on context injection with a tool calling mechanism using the OpenRouter API to support both information services and workshop operational processes. Therefore, the developed virtual assistant offers an effective, practical, and cost-efficient digital solution for supporting the digital transformation of customer services in small and medium-sized automotive workshops.